Estimation of the melting threshold of Ti supersaturated Si using time resolved reflectometry and haze measurements. (1st March 2023) - Montero, D; Caudevilla, D; Algaidy, S; Garcia-Hernansanz, R; Suler, A; Acosta-Alba, P; Kerdiles, S; Pastor, D; Garcia-Hemme, E; Roy, F; Olea, J
Abstract: Hyperdoped or supersaturated semiconductors are gathering the attention of industry and research institutions due to their sub-bandgap photon absorption properties. In this study, two fast and non-invasive techniques, time-resolved reflectometry (TRR) and Haze Measurements, are applied to infer the melt and solidification regimes of Ti supersaturated 300 mm silicon wafers, aiming to ease the characterization process towards high volume manufacturing of supersaturated materials. Ti supersaturation is attained by using an ion implantation process with a dose 3 × 10 15 cm −2, which amorphizes the surface. Crystalline quality is then recovered by means of a XeCl UV nanosecond laser annealing process. TRR technique is used to determine two different melting and solidification processes of the laser annealed implanted surface. A first brief, low temperature peak ( α peak) is associated with the melting process of the amorphized surface, followed by a longer peak/plateau ( β 1 peak/plateau), linked to the melting process of the crystalline phase below the amorphized layer, at sufficiently high laser fluences. Haze technique is used to indirectly measure the crystalline quality after the solidification process of the laser-annealed surface. Atomic force microscopy measurements are used to obtain the surface roughness value and cross-section high resolution transmission electron microscopy micrographs to check crystalline quality.